The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2174/1389202918666171016123830
|View full text |Cite
|
Sign up to set email alerts
|

Polytene Chromosomes – A Portrait of Functional Organization of the Drosophila Genome

Abstract: This mini-review is devoted to the problem genetic meaning of main polytene chromosome structures – bands and interbands. Generally, densely packed chromatin forms black bands, moderately condensed regions form grey loose bands, whereas decondensed regions of the genome appear as interbands. Recent progress in the annotation of the Drosophila genome and epigenome has made it possible to compare the banding pattern and the structural organization of genes, as well as their activity. This was greatly aided by ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 35 publications
0
45
0
1
Order By: Relevance
“…Aquamarine chromatin (former cyan) contains maximum amount of open chromatin proteins, that are the basis of the model, and occupies about 13 % of the genome. This chro matin state corresponds to 5′ UTRs of ubiquitously active genes (Zhimulev et al, 2014;Zykova et al, 2018). All the interbands with determined genomic coordinates contain this chromatin type (Zhimulev et al, 2014).…”
Section: The Model Of Four Chromatin Statesmentioning
confidence: 96%
“…Aquamarine chromatin (former cyan) contains maximum amount of open chromatin proteins, that are the basis of the model, and occupies about 13 % of the genome. This chro matin state corresponds to 5′ UTRs of ubiquitously active genes (Zhimulev et al, 2014;Zykova et al, 2018). All the interbands with determined genomic coordinates contain this chromatin type (Zhimulev et al, 2014).…”
Section: The Model Of Four Chromatin Statesmentioning
confidence: 96%
“…Developmental genes are located in the dense black bands, which are usually polygenic. It was demonstrated that, in the thinnest bands, DNA is enough predominantly for a single housekeeping gene, so the B. Judd's hypothesis "one gene-one band" was partly confirmed [40].…”
Section: Introductionmentioning
confidence: 98%
“…The development of molecular genetic methods of labeling P-element interband insertions helped to determine which types of proteins related to bands and interbands in general [27,[35][36][37]. The 4HMM mathematical model was developed using these data; it revealed four chromatin states that are distinguished by the presence of RNA polymerase II, Origin Recognition Complex (ORC), protein composition, and nucleosome modifications [38][39][40]. Aquamarine is predominantly localized in the polytene chromosome interbands, contains promoters of housekeeping genes and it is characterized by the specific set of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…active vs inactive regions) across the genome [31]. In these cells, DNA staining shows a typical banding pattern, with active genes localized in interbands, and silent, more compact, chromatin in darker bands [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%